Molecular Diagnostic and Precision Medicine in Non-Small Cell Lung Cancer. An Update on the Treatment of the Most Important Actionable Oncogenic Driver Alterations - David König; Sacha I. Rothschild (healthbook TIMES. Oncology Hematology, 2020)
Due to groundbreaking developments and continuous progress, the treatment of stage IV non-small cell lung cancer (NSCLC) has become an exciting but increasingly challenging task. This applies in particular to the subgroup of NSCLC with oncogenic driver alterations. While the treatment of epidermal growth factor receptor (EGFR)-mutated and anaplastic lymphoma kinase (ALK)-rearranged NSCLC with different tyrosine kinase inhibitors (TKI) is well established, new targets have been identified in the last years, and new TKI introduced in clinical practice. Even for *KRAS* mutations, considered for a long time as an “untargetable” alteration, promising new drugs are emerging. The detection and in-depth molecular analysis of resistance mechanisms have further fueled the development of new therapeutic strategies. The objective of this review is to give an overview of the current landscape of targetable oncogenes in NSCLC.